THE ANALYSIS OF SOCIO-ECONOMIC CHARACTERISTIC IMPACTS ON CHILD EDUCATIONIN RURAL HOUSEHOLDS - Herdiyanti Herdiyanti; M. Faisal Akbar (Sosiohumaniora, 2020)
The study titled Impact Analysis Characteristics of domestic socio-economic and child education in households in South Bangka district, this refers to the prestigious University of Bangka Belitung with the theme empowerment and strengthening Local community modalities, especially on the topic of increasing public participation on education in Bangka Belitung. The main challenge of the labor market in Bangka Belitung is the fulfillment of a more competent workforce, especially in the formal sector. This research is expected to give a real picture of the main condition causing low participation of schools in several villages in South Bangka from the side of the household. This research uses an Ordinary method of Least Square research that explains the influence of the characteristics of socio-economic households towards child education is found that the rate of household income precisely does not affect the long School children. The results showed that the age of the household head and the ratio of household dependencies had a positive influence on child education. This is in connection with work that is usually managed informally on households living in rural areas. The number of dependent households (14 to 64 years) is not going to work when the number of households in the product family is quite a lot.